Caregivers’ Knowledge Regarding Infection Prevention in Children with Hematological Cancer Attending at Tertiary Cancer Hospital, Nepal - Koirala, Sushila; Chapagain, Ashmita; Upadhyay, Hari Prasad; Neupane, Laxmi; Sharma, Sarojini (International Journal of Silkroad Institute of Research and Training, 2025)
Background: Cancer is a significant public health problem worldwide. Hematological cancers are the most common cancers, which rank 1st among childhood cancers worldwide. Hematologic cancer patients with compromised immune systems are already susceptible to infections. Infection is one of the leading causes of death in patients with hematologic cancers. The objective of the study was to assess caregivers' knowledge of infection prevention for children with hematological cancer attending the Tertiary Cancer Hospital of Nepal.Method: A cross-sectional study was conducted among 60 caregivers selected through purposive sampling. A structured interview schedule was used to collect data, and it was analyzed using SPSS version 22 and interpreted using descriptive and inferential statistics.Result: The mean age and SD of 32.53±11.179. More than half (53.3%) of respondents were female, with the majority being parents (73.3%). This study also revealed that more than three-fifths (73.3% had a good level of knowledge, one-fourth 15(25%) had a moderate level of knowledge, and only 1.7% had a low level of knowledge regarding infection prevention in children with hematological cancer. A statistically significant association was found between the caregiver’s relationship to the child and their level of knowledge (p-value = 0.013). Conclusion: This study concludes that, though the majority of the respondents had good and moderate levels of knowledge regarding infection prevention in children with hematological cancer, gaps were noted in certain areas, particularly regarding the risks of raw or undercooked food during neutropenia and the placement of plants in children’s rooms. Therefore, continuous education for caregivers is essential to address these gaps and safeguard the health of vulnerable children.